Association of FOXD1 variants with adverse pregnancy outcomes in mice and humans. Issue 10 (October 2016) - Laissue, Paul; Lakhal, Besma; Vatin, Magalie; Batista, Frank; Burgio, Gaëtan; Mercier, Eric; Santos, Esther Dos; Buffat, Christophe; Sierra-Diaz, Diana Carolina; Renault, Gilles; Montagutelli, Xavier; Salmon, Jane; et al.
Abstract : Recurrent spontaneous abortion (RSA) is a common cause of infertility, but previous attempts at identifying RSA causative genes have been relatively unsuccessful. Such failure to describe RSA aetiological genes might be explained by the fact that reproductive phenotypes should be considered as quantitative traits resulting from the intricate interaction of numerous genetic, epigenetic and environmental factors. Here, we studied an interspecific recombinant congenic strain (IRCS) of Mus musculus from the C57BL6/J strain of mice harbouring an approximate 5 Mb DNA fragment from chromosome 13 from Mus spretus mice (66H-MMU13 strain), with a high rate of embryonic resorption (ER). Transcriptome analyses of endometrial and placental tissues from these mice showed a deregulation of many genes associated with the coagulation and inflammatory response pathways. Bioinformatics approaches led us to select Foxd1 as a candidate gene potentially related to ER and RSA. Sequencing analysis of Foxd1 in the 66H-MMU13 strain, and in 556 women affected by RSA and 271 controls revealed non-synonymous sequence variants. In vitro assays revealed that some led to perturbations in FOXD1 transactivation properties on promoters of genes having key roles during implantation/placentation, suggesting a role of this gene in mammalian implantation processes.